Detoxification of cadmium from the Human Blood plasma using Dried Allium Cepa Biomass: An Equilibruim and Kinetic Study - Jibunor, V.U; Paul, S.M; Nnachi C (Research Parks Publishing LLC, 2021)
This study investigates the efficiency of Allium cepa biomass in removal Cadmium ions from aqueous solution of human blood plasma. The biosorbent was prepared and identified using FTIR which revealed the presence of carbonyl group, amide group, sulphoxide group, ether and aromatic groups. The optimum sorption was investigated and the experimental data revealed equilibrium pH 4, Cd2+ concentration 70 mgL-1 and biosorbent dose 0.80 g were obtained and used to study the equilibrium sorption rate which occurred at 80 mins with 99.98% removal at ambient temperature. The experimental data fitted Pseudo Second order kinetic as indicated by the correlation coefficient value (R2) = 0.9961 with a rate constant K2= 0.3730 g.mg-1.min-1. The experimental data conforms to Freundlich isotherm and Jovanovis isotherm, however Freundlich isotherm showed best fit with correlation coefficient (R2) = 0.632, sorption capacity (KF) = 3.3113 and sorption intensive (n) = 1.870. The separation factor of the Langmuir isotherm (RL) = 0.0141, suggests that the overall adsorption process was favourable.